Exploring the Forensic Implications of Death Cases Resulting from Airsoft Gun and Air Gun Shots: A Systematic Review of Case Reports - Muhammad Afiful Jauhani; Annisa Shalsabila Azhari; Muhammad Isra Rafidin Rayyan; Mochamad Edo Dwi Pratama; Marsha Zahra Adyanda Barus (Indonesian Journal of Legal and Forensic Sciences, 2025)
Airsoft guns and air guns are replica weapons resembling real firearms that use the force of a spring or air to fire bullets; these weapons are often considered toys and can cause fatal injury if not used properly. This study aims to highlight the forensic implications of deaths caused by airsoft guns and air guns. A systematic review was conducted by the PRISMA guidelines. Study searches were conducted on PubMed, ScienceDirect, Scopus, and Wiley databases in February 2024 to collect all published case reports. The study search and selection process resulted in 15 articles that met the inclusion criteria for qualitative synthesis. Case reports were published from 1972 to 2023 and reported from 9 countries. Victims ranged in age from 11 months to 73 years; 10 of the 15 victims were male. All deaths were caused by air gun shooting; most used a bullet size of 5.5 mm. The most common mode of death was accidental death, caused by brain injury and cardiac tamponade. In conclusion, identifying the weapon's characteristics and the injury's dynamics are essential to determine the cause of death. The most common causes are brain injury and hemorrhagic shock resulting from cardiac tamponade.